Mobilizing BIPOC Student Power against Liberalism at Soka University of America: A Collection of Voices - Huỳnh, Victoria; Storms, Kristen; Saito, Jordyn; X, Professor; Rallin, Aneil (Radical Teacher, 2021)
We write as a collective of BIPOC undergraduate activist students/organizers and contingent/tenured professors dedicated to Black, Third World, and Indigenous liberation through a feminist analysis at Soka University of America (SUA). We focus our critique on liberalism as a dominant political paradigm that has solidified the reign of empire and it’s necropolitical grips on our communities within and without SUA, our SLAC. We highlight through a brief chronology of the epistemic and physical struggles against hegemonic power exercised by our university the ways in which liberalism acts as counterrevolutionary ideology and offer critical reflections/interventions on our struggles against white supremacy at our SLAC, as well as on how our university administration utilizes “liberalism” as a technology of imperialism. We come together to resist empire from where we stand. We believe in the pedagogical possibilities of resistance.